An Exploration of Factors Linked to Academic Performance in PISA 2018 Through Data Mining Techniques - Gamazo, Adriana; Martínez-Abad, Fernando (Frontiers in Psychology, 2020)
International large-scale assessments, such as PISA, provide structured and static data. However, due to its extensive databases, several researchers place it as a reference in Big Data in Education. With the goal of exploring which factors at country, school and student level have a higher relevance in predicting student performance, this paper proposes an Educational Data Mining approach to detect and analyze factors linked to academic performance. To this end, we conducted a secondary data analysis and built decision trees (C4.5 algorithm) to obtain a predictive model of school performance. Specifically, we selected as predictor variables a set of socioeconomic, process and outcome variables from PISA 2018 and other sources (World Bank, United Nations). Since the unit of analysis were schools from all the countries included in PISA 2018 (n=21,903), student and teacher predictor variables were imputed to the school database. Based on the available student performance scores in Reading, Math and Science, we applied k-means clustering to obtain a categorized (three categories) target variable of global school performance. Results show the existence of two main branches in the decision tree, split according to the schools’ mean socioeconomic status (SES). While performance in high-SES schools is influenced by educational factors such as metacognitive strategies or achievement motivation, performance in low-SES schools is affected in greater measure by country-level socioeconomic indicators such as GDP, and individual educational indicators are relegated to a secondary level. Since these evidences are in line and delve into previous research, this work concludes by analysing its potential contribution to support the decision making processes regarding educational policies.